All-optical control of exciton flow in a colloidal quantum well complex - Yu, Junhong (2020)
Excitonics, an alternative to romising for processing information since semiconductor electronics is rapidly approaching the end of Moore's law. Currently, the development of excitonic devices, where exciton flow is controlled, is mainly focused on electric-field modulation or exciton polaritons in high-Q cavities. Here, we show an all-optical strategy to manipulate the exciton flow in a binary colloidal quantum well complex through mediation of the Förster resonance energy transfer (FRET) by stimulated emission. In the spontaneous emission regime, FRET naturally occurs between a donor and an acceptor. In contrast, upon stronger excitation, the ultrafast consumption of excitons by stimulated emission effectively engineers the excitonic flow from the donors to the acceptors. Specifically, the acceptors' stimulated emission significantly accelerates the exciton flow, while the donors' stimulated emission almost stops this process. On this basis, a FRET-coupled rate equation model is derived to understand the controllable exciton flow using the density of the excited donors and the unexcited acceptors. The results will provide an effective all-optical route for realizing excitonic devices under room temperature operation.